Risky Moms, Risky Kids? Fertility and Crime after the Fall of the Wall - Arnaud Chevalier; Olivier Marie (Center for Economic Studies and ifo Institute (CESifo), 2022)
Following the collapse of the Berlin Wall, the birth rate halved in East Germany. Despite their small sizes, the cohorts conceived during this period of socio-economic turmoil were, as they grew up in reunified Germany, markedly more likely to be arrested than cohorts conceived a few years earlier. This is consistent with negative parental selection during the period of turmoil. We highlight risk attitude as an important selection mechanism, beyond education and other observable characteristics, which explains: (i) why some women did not alter their fertility decisions during these uncertain economic times, (ii) that this risk preference was passed on to their children and (iii) that risk preference is correlated with criminal participation. Maternal selection along risk preference might thus be an important mechanism explaining the greater criminal activity of the children conceived after the fall of the Wall.
Keywords: J13; K42; 330; fertility; crime; parental selection; economic uncertainty; risk attitude